2021
DOI: 10.3892/or.2021.7998
|View full text |Cite
|
Sign up to set email alerts
|

Bcl2l10 induces metabolic alterations in ovarian cancer cells by regulating the TCA cycle enzymes SDHD and IDH1

Abstract: Bcl2-like-10 (Bcl2l10) has both oncogenic and tumor suppressor functions depending on the type of cancer. It has been previously demonstrated that the suppression of Bcl2l10 in ovarian cancer SKOV3 and A2780 cells causes cell cycle arrest and enhances cell proliferation, indicating that Bcl2l10 is a tumor suppressor gene in ovarian cancer cells. The aim of the present study was to identify possible downstream target genes and investigate the underlying mechanisms of action of Bcl2l10 in ovarian cancer cells. R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“…Succinate dehydrogenase complex subunit D (SDHD) and IDH1 were regulated by Bcl2l10. Knocking down Bcl2l10 downregulated IDH1 and SDHD and led to the accumulation of oncometabolites such as succinate and isocitrate, and therefore lead to the promotion and progression of ovarian cancer [121]. Succinate dehydrogenase is another enzyme that is a part of the TCA cycle and is primarily involved in the catalytic conversion of succinate to fumarate by oxidation [122].…”
Section: Tricarboxylic Acid Cyclementioning
confidence: 99%
“…Succinate dehydrogenase complex subunit D (SDHD) and IDH1 were regulated by Bcl2l10. Knocking down Bcl2l10 downregulated IDH1 and SDHD and led to the accumulation of oncometabolites such as succinate and isocitrate, and therefore lead to the promotion and progression of ovarian cancer [121]. Succinate dehydrogenase is another enzyme that is a part of the TCA cycle and is primarily involved in the catalytic conversion of succinate to fumarate by oxidation [122].…”
Section: Tricarboxylic Acid Cyclementioning
confidence: 99%
“…A recent study has shown the differential sensitivity of low-grade serous ovarian carcinoma cells and HGSOC cells to mTOR inhibitors [ 54 ]. Previous studies from several laboratories including ours have demonstrated the role of atypical signaling pathways such as those regulated by LPA and BCL20 in modulating the glucose metabolism in cancer cells [ 16 , 55 , 56 ]. Further interrogation of these signaling pathways in relation to specific metabolites should identify the mechanism(s) involved in the differential modulation of TCA cycle and aerobic glycolysis in these cell lines.…”
Section: Discussionmentioning
confidence: 99%